Influence of the Principal2019;s Communication Skills on Students2019; Discipline in Public Day Secondary Schools in West Pokot Sub County, Kenya (Global Journal of Human-Social Science, 2021)
Ethical instructional leadership demonstrates that the success of any teaching and learning process and the level of students discipline is dependent on effective communication skills Learning and the success of student discipline are among the most primary goals of a principal s instructional leadership This study therefore investigated the influence of the principal s communication skills on student discipline in secondary schools in West Pokot Sub County in Kenya The study was anchored on deontological ethical and teleological ethical theories which typically judge rightness or wrongness of an individual s actions in his or her line of duty and if the actions are fair to the followers The target population of the study was 3450 respondents This comprised of 497 teachers and 2953 students from the public day secondary schools in the study area Simple random and purposive sampling techniques were used to arrive at a sample of 593 respondents Questionnaires interview and document analysis were used as the primary tools of data collection The study used a descriptive survey research design in data analysis using SPSS version 26 to obtain mean values and standard deviation
Keywords: principal2019; s communication skills; students2019; discipline; public day secondary schools